1998
DOI: 10.1111/j.1399-3038.1998.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in children with initial low birth weight

Abstract: The objective of this analysis was to examine the effect of low birth weight and prematurity on bronchial air-flow, bronchial reactivity, airway symptoms and asthma diagnosis at school age. A cross-sectional epidemiological study was performed in three small towns in the eastern part of Germany on 2470 school children aged 5-14 (89.1% of eligible children). A 78 item questionnaire to determine risk factors at birth and in early childhood was employed. 7.8% of the children were born before completing 38 gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 39 publications
3
35
0
6
Order By: Relevance
“…Methods of pulmonary function measurements are described elsewhere (Frye et al 2001;Wjst et al 1998). Briefly, technicians were trained thoroughly at the beginning of each survey.…”
Section: Ambient Pollutionmentioning
confidence: 99%
“…Methods of pulmonary function measurements are described elsewhere (Frye et al 2001;Wjst et al 1998). Briefly, technicians were trained thoroughly at the beginning of each survey.…”
Section: Ambient Pollutionmentioning
confidence: 99%
“…Rona and colleagues studied children aged 5-11 years and reported that lung function measurements, except forced midexpiratory flow between 25 and 75% of vital capacity (FEF 25-75% ), were positively associated with birthweight, but respiratory symptoms were associated with prematurity (10). Wjst and colleagues (11) reported decreased total lung capacity and peak expiratory flow rates, but increased bronchial reactivity and asthma in 5-14 year olds who were born with LBW.…”
mentioning
confidence: 99%
“…Generally speaking, BW is one of several factors which may affect lung function and could predict future lung development. Usually this issue has been analyzed in children [6] in terms of very LBW, which is connected with many pre-and perinatal disturbances [2,3]. Our study was performed on a sufficiently large number of adult patients, and we attempted to demonstrate the influence of different BW quartiles on the most important spirometric parameters in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of asthma in males with BW < 2501 g was higher than in males with a BW between 3001-3500 g. Their other findings indicated that fetal growth retardation rather than preterm delivery of male infants was the main risk factor for developing asthma. Another study, performed by Wjst et al [6] on 2470 school children aged between 5-14 years, found that bronchial hyperresponsiveness was significantly increased in the examined group with LBW compared to normal term born children with correct BW (p < 0.001). Moreover, asthma was also more frequent in term born children with LBW.…”
mentioning
confidence: 91%
See 1 more Smart Citation